Stigmatization of Muslim in Karim Miské’s Arab Jazz: an Orientalism Study - Hidayah, Lutfi Nur; Djohar, Hasnul Insani (Universitas Lambung Mangkurat, 2023)
Although Islam is the second largest religion in France, it is still a minority compared to the overall population. As in other Western countries, Muslims who are in the minority find it difficult to adapt to their surroundings. Apart from the significant cultural differences, mistreatment by the local population, such as isolation and neglect, is also a contributing factor. Muslims have long been the subject of ridicule and victims of the bad stigma of Western society, various slanders are directed at Muslim minorities there with the assumption that Muslim minorities in the West are very easy to be used as scapegoats for all the actions they have committed. Of the many previous studies that discuss how Muslim minorities struggle to survive in an environment that often discriminates against them because of differences in culture and appearance, researchers rarely or almost do not find research that discusses how Muslim minorities survive being scapegoated by Westerners in murder cases in the area where they live there. The researchers here want to focus on how Muslims face various discriminations, especially being scapegoated by Westerners in Karim Miské's Arab Jazz. By using a qualitative approach, the researchers collected and analyze the data using Said’s orientalism theory as the main theory, Goffman’s stigma theory and Bhabha’s mimicry as the supporting theory to classify the stigma and explain the resistance towards the Muslim stigmatization.